Tactile event-related potentials in amyotrophic lateral sclerosis (ALS): Implications for brain-computer interface. Issue 1 (January 2016) - Silvoni, S.; Konicar, L.; Prats-Sedano, M.A.; Garcia-Cossio, E.; Genna, C.; Volpato, C.; Cavinato, M.; Paggiaro, A.; Veser, S.; De Massari, D.; Birbaumer, N.
Highlights: Implementation of a tactile event-related paradigm for severely paralyzed people. No event-related potential pathology in patients with amyotrophic lateral sclerosis. Discussion of implications for brain-computer interfaces in paralyzed patients. Abstract: Objective: We investigated neurophysiological brain responses elicited by a tactile event-related potential paradigm in a sample of ALS patients. Underlying cognitive processes and neurophysiological signatures for brain-computer interface (BCI) are addressed. Methods: We stimulated the palm of the hand in a group of fourteen ALS patients and a control group of ten healthy participants and recorded electroencephalographic signals in eyes-closed condition. Target and non-target brain responses were analyzed and classified offline. Classification errors served as the basis for neurophysiological brain response sub-grouping. Results: A combined behavioral and quantitative neurophysiological analysis of sub-grouped data showed neither significant between-group differences, nor significant correlations between classification performance and the ALS patients' clinical state. Taking sequential effects of stimuli presentation into account, analyses revealed mean classification errors of 19.4% and 24.3% in healthy participants and ALS patients respectively. Conclusions: Neurophysiological correlates of tactile stimuli presentation are not altered by ALS. Tactile event-related potentials can be used to monitor attention level and task performance in ALS and may constitute a viable basis for future BCIs. Significance: Implications for brain-computer interface implementation of the proposed method for patients in critical conditions, such as the late stage of ALS and the (completely) locked-in state, are discussed.